Juridical Review of the Performance of the State Civil Apparatus According to Law Number 5 of 2014 in the Kokalukuna District of Baubau City - I K Dewi; Yoga Subiyanto (Research institutions and community service Universitas Muhammadiyah Buton, 2020)
Employee performance is very influential on organizational performance in carrying out tasks and achieving its goals, because employees are the driving force of the organization. This study aims: (1) To find out how the implementation of the performance of the State Civil Apparatus based on Law Number 5 of 2014. (2) To determine what factors are hampering the improvement in the performance of the State Civil Apparatus based on Law Number 5 of 2014. Research This uses a normative juridical qualitative approach, which is intended to understand the phenomena about what is experienced by the research subjects. The results showed that the implementation of the performance of the State Civil Apparatus (SCA) in the Kokalukuna District Office namely (1) Still not fully optimal based on Law Number 5 of 2014, this can be seen from the lack of adequate human resources in which office officials/employees Kokalukuna District in providing services to the community there is still the term selective logging. So that the community in taking care of something in the district office still feels difficulties. (2) Not optimal due to the lack of government officials as evident from the vacant position of the Head of the Public Service Section, making the service at the sub-district office less than the maximum felt by some members of the community. (3) Factors that hinder the improvement of ASN performance based on Law number 5 of 2014 in the Kokalukuna District Office, namely: (1) Effect of Discipline on Performance; (2) Effects of Education and Training on Performance; (3) Effect of Work Atmosphere on Performance; (4) Human Resource Development Strategy.